Posterior Reversible Leukoencephalopathy Syndrome in a Pre-Eclamptic Woman - Raghvendra Thakur; Bhoj Raj Sharma; Tian Yuan; Zheng Guiying (Hindawi Limited, 2013)
Posterior reversible leukoencephalopathy syndrome (PRLS) is a neurologic condition, often presents with various clinical manifestations. It is rare during pregnancy. We herein report a case of PRLS in a 31-year-old woman, presented with preeclampsia, diagnosed by computer tomography, and successfully delivered the baby with caesarean section. At discharge, patient was fully recovered without any complication.